Perampasan Aset dalam Upaya Pemulihan Aset Hasil Tindak Pidana Korupsi di Indonesia - Khairunnisa Dhiavella Asy’ari; Nathalina Naibaho (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
Corruption is a criminal offense that causes disproportionate losses to state finances or the economy of a country and inhibits the growth and continuity of national development. According to the Indonesian Corruption Watch (ICW), the total loss of Indonesian state finances due to corruption in 2023 is 28.4 trillion rupiah. This paper discusses the asset forfeiture policy as a form of law enforcement that can be carried out in an effort to recover assets against corruption crimes through civil law mechanisms, which are also carried out in conjunction with criminal enforcement, to maximize the return of state losses due to corruption crimes.